Is the Cost-effectiveness of Mechanical Thrombectomy Universal? A Systematic Review of Cost utility of Mechanical Thrombectomy. (16th November 2020) - Waqas, Muhammad; Levy, Bennett; Vakharia, Kunal; Dossani, Rimal Hanif H; Tso, Michael K; Davies, Jason; Levy, Elad I; Siddiqui, Adnan H
Abstract: INTRODUCTION: Over past the past few years mechanical thrombectomy has become the standard of care for large vessel occlusion stroke patients. Despite the extra cost of endovascular mechanical thrombectomy (MT) procedure costs more than traditional medical management and intravenous thrombolysis for stroke. However, considering the improvement in functional outcomes and lower rates of disability with MT, several studies have reported MT to be cost effective. The cost effectiveness estimates depend on the cost of procedure and rehabilitation which is varies across different regions. METHODS: We searched PubMed, Cochrane and EMBASE to include studies on the cost effectiveness of mechanical thrombectomy published over a period of 10 years i.e., January 2010-March, 2020. We used "cost effectiveness", "cost utility", "mechanical thrombectomy" and "endovascular treatment of stroke" were used in different combinations. The country of cost effectiveness assessment, assumptions about cost of mechanical thrombectomy and rehabilitation, and efficacy input used for cost effectiveness analysis were recorded. RESULTS: Fifteen studies from 8 countries in 4 continents were included in the study. Six of these studies were from the US. Two studies from France, 1 from Netherlands, 2 from United Kingdom, 1 from Canada, 1 from China, 1 from Sweden and 1 from Australia. Cost per quality of life year (cost/QALY) was the most commonly reported outcome. Cost per QALY ranged from 3110 US $ (USA) to 14, 881 US $ (France). The most common source of efficacy data was meta-analysis of mechanical thrombectomy clinical trials (N = 5) followed by SWIFT PRIME (N = 3), MERCI (N = 3), MR CLEAN (N = 1), THRACE (N = 1) and expert panel opinion (N = 1). One study used efficacy input from 5 different clinical trials. Using a willingness to pay threshold of 50, 000 USD, all studies concluded that MT was cost effective irrespective of the efficacy model used. CONCLUSION: Mechanical thrombectomy is more cost effective than medical management and intravenous thrombolysis across various health systems in different countries. The cost benefit persists regardless of the efficacy model used.